2021
DOI: 10.3390/app11188563
|View full text |Cite
|
Sign up to set email alerts
|

Review of Materials and Fabrication Methods for Flexible Nano and Micro-Scale Physical and Chemical Property Sensors

Abstract: The use of flexible sensors has tripled over the last decade due to the increased demand in various fields including health monitoring, food packaging, electronic skins and soft robotics. Flexible sensors have the ability to be bent and stretched during use and can still maintain their electrical and mechanical properties. This gives them an advantage over rigid sensors that lose their sensitivity when subject to bending. Advancements in 3D printing have enabled the development of tailored flexible sensors. Va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…The principal effect was represented by damage of bacterial enzymes in glycolysis and tricarboxylic acid cycle determining the stalling of the oxidative branch of the tricarboxylic acid cycle. Furthermore, an article published in 2019 confirmed that silver ions target glyceradldehyde-3-phosphate dehydrogenase in glycolysis in E. coli [105,106].…”
Section: Therapies Using Agnps Per Se In the Eradication Of Helicobac...mentioning
confidence: 98%
See 1 more Smart Citation
“…The principal effect was represented by damage of bacterial enzymes in glycolysis and tricarboxylic acid cycle determining the stalling of the oxidative branch of the tricarboxylic acid cycle. Furthermore, an article published in 2019 confirmed that silver ions target glyceradldehyde-3-phosphate dehydrogenase in glycolysis in E. coli [105,106].…”
Section: Therapies Using Agnps Per Se In the Eradication Of Helicobac...mentioning
confidence: 98%
“…The principal effect was represented by damage of bacterial enzymes in glycolysis and tricarboxylic acid cycle determining the stalling of the oxidative branch of the tricarboxylic acid cycle. Furthermore, an article published in 2019 confirmed that silver ions target glyceradldehyde-3-phosphate dehydrogenase in glycolysis in E. coli [ 105 , 106 ]. The potential action of silver ions against bacteria should be taken into consideration as a better antimicrobial alternative treatment reducing the risk of antibiotic resistance.…”
Section: Alternative and Complementary Agnps-based Approaches In The ...mentioning
confidence: 99%
“…Flexible sensors with force sensing are highly favored by researchers due to the potentially huge applications in robotics, health and medicine, and artificial intelligence . Flexible sensors based on novel nanomaterials and flexible materials are meeting the emerging need, as the mechanical properties of flexible materials and the high sensitivity of nanomaterials can break the upper limit of deformation to better achieve perfect contact on irregular surfaces …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Up to now, there has been a lot of research effort spent trying to resolve the above challenges. [23][24][25][26] For instance, various 3D printing techniques (ink-based and light-based) have been applied in printing conductive hydrogels, offering more options for the customized application. Abundant material synthesis routes have been proposed to prepare printable hydrogels with good conductivity, stretchability, and functionality.…”
Section: Introductionmentioning
confidence: 99%